The European Union and political behaviour: The shadow of the Great Recession - Lobo, Marina Costa (2021)
The symposium aims to analyse the politicisation of the European issue following the onset of the Eurozone crisis, in particular its impact on individual attitudes and voting both at the national and supranational level. By way of an introduction, we address the state of the art on the importance of the Eurozone crisis for EU politicisation, as well as outlining each article and its contribution. While our authors may sometimes focus on different dependent variables, they all speak to the question of whether the Great Recession made a lasting difference, and whether EU politicisation matters. Most articles are longitudinal, and test for changes due to the crisis (Dassonneville, Lewis- Beck and Jabbour; Ruiz-Rufino; Talving and Vasilopoulou; Jurado and Navarrete). But preoccupation with the Great Recession is also present in the articles assessing the political learning that unfolded from it (Ruiz-Rufino), or the ones which investigate whether EU effects can be detected during the post-crisis years (Talving and Vasilopoulou; Lobo and Pannico; Heyne and Lobo). Despite the diversity of approaches, and certain differences in findings, each article contributes to a major debate ongoing in the literature, especially three key debates which have arisen: the crisis’ impact on European party systems, economic voting, and the degree of legitimacy of democratic systems.